Польська публіцистика 20-30-х років ХХ ст. про творчість Тараса Шевченка - Кравченко, Світлана Іванівна; Kravchenko, Svitlana I. (Волинський національний університет імені Лесі Українки, 2008)
У статті розглядаються публікації, присвячені різним аспектам життя і творчого шляху українського поета. Особлива увага звертається на особисті стосунки Шевченка з поляками та їх вплив на творчість. The article „The Polish publicistic at the 20th−30th years of XX century about the creation of Taras Shevchenko” is about publications, which where devoted different aspects of life and creative way of Ukrainian poet. The main attention to personal relationship between Shevchenko and polish nation and there influence on his creation.
Polish Publicism of 20−30-х Years of ХХ item is About Creation of Shevchenko
Keywords: статті; articles; впливи; influences; стосунки; relations; відгуки; reviews; переклади; translations